Culture and Unmerited Authorship Credit: Who Wants It and Why? - Ren, Xiaopeng; Su, Hong; Lu, Kewen; Dong, Xiawei; Ouyang, Zhengzheng; Talhelm, Thomas (Frontiers in Psychology, 2016)
Unmerited authorship is a practice common to many countries around the world, but are there systematic cultural differences in the practice? We tested whether scientists from collectivistic countries are more likely to add unmerited coauthors than scientists from individualistic countries. We analyzed archival data from top scientific journals (Study 1) and found that national collectivism predicted the number of authors, which might suggest more unmerited authors. Next, we found that collectivistic scientists were more likely to add unmerited coauthors than individualistic scientists, both between cultures (Studies 2-3) and within cultures (Study 4). Finally, we found that priming people with collectivistic self-construal primes made them more likely to endorse questionable authorship attitudes (Study 5). These findings show that culture collectivism is related to unmerited authorship.